Role of P&I Insurance in Implementing Amendments to Maritime Labour Convention 2014 - Petrinović, Ranka; Lovrić, Ivana; Perkušić, Trpimir (Transactions on Maritime Science, 2017)
Maritime Labour Convention (MLC), 2006 stipulates mandatory financial security for repatriation costs (Standard A 2.5), and contractual compensations related to death or longterm disability of seafarers due to an occupational injury, illness or hazard (Standard A 4.2) that is to be provided by the shipowner. However, financial security system set in the MLC was prescribed very broadly and insufficiently precise and, therefore, it opened a number of questions and doubts. Among others, the following questions are particularly interesting: what the legal nature of the MLC financial security is; from the insurance standpoint, whether this is life or accident insurance, or it is liability insurance; who has an insurable interest and what the nature of that interest is; which document proves fulfilment of MLC requirements. Due to the necessity of improving financial security provisions, in 2014 Amendments to the MLC were adopted that came into force in January 2017. Although the MLC does not explicitly prescribe a system of compulsory insurance, with the third injured party the right to a direct claim (actio directa) towards the liability insurer, marine insurance given its characteristic, appeared as a very suitable method of fulfilling MLC requirements – especially P&I insurance. All the clubs within the International Group of P&I Clubs have agreed to assist their members (shipowners) in complying with these additional financial security requirements under the Amendments to the MLC and issue MLC Certificates to their members. MLC Certificates refer to the MLC Extension Clause, 2016 and thus subject the insurance to conditions and limitations in the said clause. MLC Extension Clause provisions will be added to clubs P&I Rules which form the standard P&I cover.